COMPARATIVE STUDY BETWEEN DIFFERENT SOLAR RADIATION SHIELDING MATERIALS - Aditya Ghanekar (International Educational Journal of Science and Engineering, 2025)
This paper explores different methods to protect satellites from outer space radiation, primarily Coronal Mass Ejections (CMEs). It discusses what CMEs are and how they damage satellites. It also briefly discusses different ways to deal with such kinds of SPE, like Active Shielding, Passive Shielding, Radiation Hardening, and Redundancy. The research focuses on passive shielding and compares various materials, taking into account factors such as cost, shielding capability, and effectiveness.